Интегральное уравнение на [-1, 1] с логарифмическим ядром - Полянская, Татьяна Семеновна (НТУ "ХПИ", 2016)
Рассмотрено интегральное уравнение первого рода с логарифмическим ядром, к которому приводит ряд задач дифракции волн. Проведена дискретизация этого уравнения на основе метода дискретных особенностей. Введены пары гильбертовых пространств и операторы в них, соответствующие заданной и дискретной задачам. С их помощью доказана однозначная разрешимость дискретной задачи и дано строгое обоснование оценки скорости сходимости решения дискретной задачи к точному решению интегрального уравнения.

We consider an integral equation of the first kind with a logarithmic kernel, which arises in a number of problems of wave diffraction. The equation is discretized using the method of discrete singularities. We introduce a pair of Hilbert spaces and operators in them, corresponding to the given and the discrete problems. With their help, we prove the unique solvability of the discrete problem and justify rigorously the rate of convergence of the solution of the discrete problem to the exact solution of the integral equation.
Integral equation on [-1, 1] with a logarithmic kernel
Keywords: математическая физика; метод дискретных особенностей; логарифмические особенности; квадратурные формулы; integral equations; logarithmic kernel; method of discrete singularities